Implementation of an Electronic-Based Government System (SPBE) at the Muaro Jambi Regency Communication and Information Service - Oktarina, Dwi (Sustainability (STPP) Theory, Practice and Policy, 2023)
This research aims to investigate the implementation, inhibiting factors, and actions taken in the implementation of the electronic-based government system in the Muaro Jambi District Communication and Informatics Office. This research uses a qualitative method with a qualitative descriptive approach and collects data through observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of the electronic-based government system in the Muaro Jambi District Communication and Informatics Office plays a crucial role in enhancing government efficiency and transparency. The main obstacle in the implementation of this system is the lack of human resources with adequate information technology knowledge. To address this challenge, the Muaro Jambi District Communication and Informatics Office needs to enhance the competencies of human resources in the field of information technology. Therefore, it can be concluded that the implementation of the Electronic-Based Government System (SPBE) in the Muaro Jambi District Communication and Informatics Office has not achieved optimal results, as evident from the actions taken.